DESIGN AND CONSTRUCTION OF ONLINE LIBRARY INFORMATION SYSTEM FOR STMIK INDONESIA CAMPUS, BANDA ACEH WEB -BASED - Sufyan; Maimun; Yonoriadi; Dara Zulfinar; Ismail; Riyan Maulana; Nurjanah Ismail (CV Naskah Aceh, 2025)
In the current digital era , the development of information and communication technology has had a significant impact on various aspects of life, including in the world of education. One of the important things in education is access to adequate information sources. Currently, the library system used at the STMIK Indonesia Banda Aceh campus still uses conventional methods with physical libraries , which can cause limited access, delays in obtaining information sources , and limitations in managing and maintaining book collections. STMIK Indonesia Banda Aceh has a library that still uses a manual recording system or bookkeeping in conducting transactions, which will certainly increase the difficulty in processing library data, not to mention errors in book borrowing and returning transactions, as well as other reporting errors . Based on the results of the library website system design at STMIK Indonesia Banda Aceh , the results show that the system can carry out the online loan registration process and fine notifications. The author hopes that in creating this library information system, it can help facilitate staff and all related parties in processing library data effectively and efficiently.